E-Government Service Quality Using E-GovQual Dimensions Case Study Ministry of Law and Human Rights DIY - Wijatmoko, Taufiq Effendy (Proceeding International Conference on Science and Engineering, 2020)
Regional Office of the Ministry of Law and Human Rights DIY organizes a variety of public services using information technology, including correctional services, immigration services, general legal administration services, intellectual property services, communication services, data and information services, and others administrative services. All of these services cannot be separated from the role of information technology to provide services that are fast, cheap, effective and reliable to the public. This study was conducted to assess the quality Ministry of Law and Human Rights DIY e-Government service using e-GovQual dimensional framework as a best practice. This study include quantitative research involving a number of respondents for the survey. This research question based on the dimensions of e-Govqual and represent the attributes of each dimension of e-GovQual to assess the quality of Ministry of Law and Human Rights DIY e-Government service. The question must pass the validation test using Cronbach’s ?. The processing of data using confirmatory factor analysis to obtain the main factors that affect each of the dimensions of e-GovQual. The Importance Performance Analysis (IPA) method helps e-Govqual to measure the level of importance and level of performance of each e-Govqual attribute by classifying it in the Cartesian quadrants, which can help ensure the quality of e-Government services according to the needs and expectations of citizens as service user. Values in IPA (concentrating here, continuing to work well, low priority, and possibly overdoing it) will be the value of quality e-Government services. The results of this study are expected to give priority as a recommendation for Information and Communication Technology to the development of e-Government services in order to improve service quality.